Calcium anacardate in the diet of broiler chickens: the effects on growth and bone quality - Cruz, Carlos Eduardo; Freitas, Ednardo; Aguiar, Germana; Braz, Nádia; Trevisan, Maria Teresa (Revista Ciência Agronômica, 2019)
The aim of this research was to evaluate the effects of adding calcium anacardate (ACa) as a source of anacardic acid to the diet of broiler chickens on the growth, quality and bone composition of the femur and tibia of the birds. A total of 840 male chicks, one day old, were kept in a completely randomised experimental design, with six treatments and seven replications of 20 birds. The following treatments were applied: a diet without the addition of growth promoter (GP), a diet with added GP and other diets with no GP and the addition of ACa at levels of 0.25, 0.50, 0.75 and 1%. The variables under analysis were the weight, length, diameter, Seedor index, and the resistance and deformity of the left femur and tibia of the birds. For bone composition, the dry matter and mineral matter of the right femur and tibia of the chickens were analysed. There were no significant differences between treatments in the growth, quality or composition of the femur or tibia of the birds, showing that the use of calcium anacardate as a source of anacardic acid does not affect bone deposition in broiler chickens up to 42 days of age.